Novel TNFAIP3 microdeletion in a girl with infantile-onset inflammatory bowel disease complicated by a severe perianal lesion - Taniguchi, Kosuke (Hum Genome Var, 2021)
A20 haploinsufficiency (HA20), a disease caused by loss-of-function TNFAIP3 mutations, manifests various autoinflammatory and/or autoimmune symptoms. Some cases of HA20 were initially diagnosed as very early onset inflammatory bowel disease (VEO-IBD). We performed whole-exome sequencing (WES) for a Japanese girl with infantile-onset IBD and a severe perianal lesion and detected a novel de novo 119 kb microdeletion containing only TNFAIP3 (arr[GRCh37] 6q23.3(138125829_138244816) × 1).